2020
DOI: 10.3390/v12050536
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Bronchitis Virus Regulates Cellular Stress Granule Signaling

Abstract: Viruses must hijack cellular translation machinery to express viral genes. In many cases, this is impeded by cellular stress responses. These stress responses result in the global inhibition of translation and the storage of stalled mRNAs, into RNA-protein aggregates called stress granules. This results in the translational silencing of the majority of mRNAs excluding those beneficial for the cell to resolve the specific stress. For example, the expression of antiviral factors is maintained during viral infect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 70 publications
2
10
0
Order By: Relevance
“…consistent with previous reports [43], also in our study we found that IBV inhibits both eIF2αdependent (heat shock, sodium arsenite) and -independent (NaCl) SGs formation. We also assessed SGs formation by PEDV infection, only 10%-20% of PEDV-infected Vero cells were SGs positive (S6 Fig).…”
Section: Plos Pathogenssupporting
confidence: 94%
See 3 more Smart Citations
“…consistent with previous reports [43], also in our study we found that IBV inhibits both eIF2αdependent (heat shock, sodium arsenite) and -independent (NaCl) SGs formation. We also assessed SGs formation by PEDV infection, only 10%-20% of PEDV-infected Vero cells were SGs positive (S6 Fig).…”
Section: Plos Pathogenssupporting
confidence: 94%
“…During the course of our study, it was reported that IBV inhibits eIF2α-dependent and -independent SGs induction in Vero cells [ 43 ]. Here, we used H1299 and DF-1 cells to further investigate the inhibition of SGs by IBV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While sequestration of viral RNAs in SGs is generally thought to represent an antiviral strategy, it is also possible that in some cases, viral replication might benefit from the concentration of viral RNAs in SGs. Given that many viruses including poliovirus, infectious bronchitis virus, mengovirus, and TMEV efficiently prevent the recruitment of viral RNAs into SGs [280,[374][375][376], it is reasonable to postulate that SGs primarily serve an antiviral function.…”
Section: Sequestration Of Viral Rnas In Sgs or Sg-like Structuresmentioning
confidence: 99%